Endovascular Treatment of Incidentally Found Multiple Aneurysms Originating from a Bronchial Artery: A Case Report - Minhyeok Yoon; Jung Guen Cha; Jongmin Park; Sang Yub Lee; See Hyung Kim; Jihoon Hong; Byunggeon Park (Journal of the Korean Society of Radiology, 2023)
Bronchial artery aneurysm (BAA) is a rare disease, and multiple aneurysms of a single bronchial artery are rarer. Regardless of the size of the lesion, it is at risk of rupture and can cause massive hemoptysis or severe pain. We report a rare case of bronchial artery embolization (BAE) of multiple aneurysms of a single bronchial artery. During medical examination, a 64-year-old female was diagnosed with multiple BAAs and endobronchial lesions in the right lower lung on CT 10 years prior to presentation to our hospital. Further evaluation of the lesions was recommended; however, the patient was lost to follow-up. The patient complained of dyspnea and visited our hospital, and the size of the BAA had increased on CT. BAE was done successfully using N-butyl-2-cyanoacrylate and detachable coils. Follow up CT after BAE showed significant decrease in extent of inflammatory lesion in the right lung.